The Aging and Old Age Process: Construction and Validation of an Attitude Scale. - Luiz, Karine Kátia Iria; Saraiva de Loreto, Maria das Dores; Ferreira, Marco Aurélio Marques; Mafra, Simone Caldas Tavares (Ageing International, 2023)
The aim of this article is to present the construction and validation of an attitude scale for the older adults towards aging and old age. A quantitative, descriptive approach was used, and the population is of older adult residents in the city of Rio Paranaíba, Minas Gerais, Brazil, with a total of 252 participants. Data were collected using the snowball technique, and the statistical technique of Factor Analysis was used for the data analysis. As a result, it was obtained a scale with 19 items, grouped into seven factors (personal relationships, autonomy and independence, intergenerationality, resilience, resignation, receptivity and expenses) covering five dimensions (cognitive, biological, psychological, social and economic). It can be concluded that the scale has indicative variables in several studies on aging and old age, making it an appropriate instrument in the area of applied social sciences for measuring the attitude of the older adults.